THE LEGAL STANDING OF THE ADAT COMMUNITY OF YAWAONAT AS A PROPOSER IN THE MATERIAL EXAMINATION OF THE ARTICLE 20 LETTER A OF THE LAWS NUMBER 21/2001 IN THE CONSTITUTIONAL COURT - Kambuaya, Ruth (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 3 No 1 (2014)DO - 10.24843/JMHU.2014.v03.i01.p10, 2014)
The substance of legislation is a written legal norm which has a binding and constant legal power. Substantially, the Article 20 section 1 letter a of the Laws Number 21/2001 has violated the constitutional rights of the adat community of Yawaonat. In this connection the adat community has made a proposal for material examination against Laws Number 21/2001 to the Constitutional Court. This study describes the rights of the adat community in accommodating outsiders (non-Papuan people) to become the Native of Papuans based on the adat law which has been accommodated in the Laws Number 21/2001. The material examination conducted by the Constitutional Court decided that the significance for recognizing outsiders to become the Native of Papuans if it is not well signified will create constitutional losses for outsiders who have been recognized as the native Papuans and can harm the constitutional rights of the adat community. This is a normative legal study. The legal sources employed for this study was the legal primary and secondary sources. The analysis was done systematically and interpretatively with juridical evaluations. The legal standing of the adat community of Yawaonat as a proposer in the session of the Constitutional Court is based on the specifications of Article 51 section 1 of the Laws Number 24/2003 with reference to the Laws Number 8/2011 concerning Constitutional Court. The rights of the adat community which is violated covers the constitutional rights given by the 1945 Constitution and the rights by Laws Number 21/2001
Keywords: Legal standing, Adat community, Laws examinat